Invoking pairwise interactions in water-promoted diels-alder reactions by using ionic liquids as cosolvents - Manna, Arpan; Kumar, Anil (Chemphyschem, 2014)
Rate constants and derived activation parameters of organic reactions in aqueous media, in particular Diels-Alder reactions, are sensitive to the presence of cosolvents in water. To enhance the solubility window of water, we introduced ionic liquids as cosolvents in the aqueous Diels-Alder reaction between anthracene-9-carbinol and N-ethylmaleimide. The reactive potentials of the organic compounds are parameterized by using semi-empirical quantum chemical methods. The principle of Savage-Wood additivity of group interactions is used to quantify the pairwise group interactions among chemically inert ionic liquids and organic reactants, both at initial and transition states of the reaction. The present approach shows promise, as the use of simple calculations from easily available kinetic data can help researchers to understand the versatility of green ionic-liquid alternatives to volatile organic solvents.